Analisis kadar pulangan pendidikan di Malaysia - Rahmah Ismail,; Nanthakumar Loganathan, (penerbit ukm, 2007)
This paper analysis the rate of return from investment in education at the primary, secondary, tertiary and some selected courses in the public higher learning institutions by using Cost and Benefit Analysis (CBA). The main reason for this analysis is to compare impact of investment in education on ‘human capital’ accumulation based on social and private the return. The result of this study is very useful to look forward at the importance of investment in education. Previous studies have been used several methodology to analyse the rate of return from investment in education and from that a lot of conclusion had been discussed. Anyway, in this study the ways of educational costing in Malaysia had been showed clearly and try to analysis the rate of return in education from various situations by using the Elaborate and Short-cut Method. Finally, a few miscellaneous aspects about the rate of return measurement in this analysis should be highlight clearly because the private and social rate of return result in each level of education is not equal.